Avaliação da implementação da previdência complementar com alcance no Tribunal de Contas do Estado do Ceará - Sabóia, Isabel Cristina (2024)
When conceptualizing the social security system, Campos (2022) highlights that it consists of the set of norms, rules and principles that govern the social security discipline of a certain group of human beings. For public servants, primarily, their systems are provided for in article 40 of the Federal Constitution of 1988, which sometimes undergoes reformulations. Due to its relevant context, it is worth noting that the last social security reform resulting from Constitutional Amendment (EC) No. 103/2019 established that federated entities must establish a supplementary social security system for their employees. The Complementary Social Security System (RPC) aims to offer additional social security security to that in addition to the benefits assured by the General and Own System. Given this context, this study aims to evaluate the implementation of the Supplementary Pension Regime (RPC) model of the Government of the State of Ceará with the scope of the Court of Auditors of the State of Ceará (TCE/CE). For this analysis, the methodology consisted of a qualitative approach, carried out through bibliographic and documentary research. Furthermore, to achieve its objectives, data collection was carried out through participant observation and the application of semi-structured open interviews, in order to support the dimensions of the in-depth evaluation perspective of Lea Rodrigues (2008) with the analytical contributions of the evaluation of the implementation of public policies and programs suggested by Lima and Mendes (2021). Data analysis was developed through content analysis from the perspective of Bardin (2011), with the dimensions categorized according to the themes. Based on the analysis of these dimensions and the concepts explained by the interlocutor, it was possible to observe how CE PREVCOM emerged as a Closed Entity for Supplementary Pensions, in accordance with constitutional and legal mandates, and that the actions developed to reach the civil servants, according to the management criteria, came as one of the ways to address the actuarial deficit of the State of Ceará and try to balance this entire trajectory of pensions, both in its own and supplementary regimes, which is why the good progress of the Pension Fund is important and fundamental.